A new millipede, Austrotyla awishoshola n. sp., (Diplopoda, Chordeumatida, Conotylidae) from New Mexico, USA, and the importance of cave moss gardens as refugial habitats - Wynne, J. Judson; Shear, William A. (Zootaxa, 2016)
Austrotyla awishoshola n. sp. is described from the moss gardens of one lava tube cave in El Malpais National Monument, Cibola Co., New Mexico. Most chordeumatidans require mesic conditions, and these environments are limited to moss gardens in several cave entrances and beneath cave skylights in El Malpais. Presently, this species is known from the moss gardens of a single of cave in the monument. We suggest A. awishoshola may be a climatic relict, having become restricted to the cave environment following the end of the Pleistocene. We discuss the importance of cave moss gardens as refugial and relictual habitats. Recommendations are provided to aid in the conservation and management of A. awishoshola and these habitats.